Athletes` evaluations of their head coach`s coaching competency - Myers, N. D.; Feltz, D. L.; Maier, K. S.; Wolfe, E. W.; Reckase, M. D. (Research Quarterly for Exercise and Sport, 2006)
This study provided initial validity evidence for multidimensional measures of coaching competency derived from the Coaching Competency Scale (CCS). Data were collected from intercollegiate men`s (n = 8) and women`s (n = 13) soccer and women`s ice hockey teams (n = 11). The total number of athletes was 585. Within teams, a multidimensional internal model was retained in which motivation, game strategy, technique, and character building comprised the dimensions of coaching competency. Some redundancy among the dimensions was observed. Internal reliabilities ranged from very good to excellent. Practical recommendations for the CCS are given in the Discussion section.